Gender violence: interdisciplinary perspectives - O'Toole, Laura L.; Schiffman, Jessica R.; Edwards, Margie L. Kiter (New York Univ. Press, 2007)
The origin of the family, private property, and the state / Friedrich Engels -- The construction of masculinity and the triad of men's violence / Michael Kaufman -- The socio-cultural context of rape : a cross-cultural study / Peggy Reeves Sanday -- "Need : a chorale for Black woman voices" / Audre Lorde -- Sexual coercion in American life / Edwin Schur -- Contextualizing men's violence : the personal meets the political / Michael Kimmel -- Sexual terrorism / Carole J. Sheffield -- "Anatomy lesson" / Cherríe Moraga -- Changed women and changed organizations : consequences of and coping with sexual harassment / Barbara A. Gutek and Mary P. Koss -- Sexual harassment in organizations : a critique of current research and policy / Christine L. Williams -- The confluence of race and gender in women's sexual harassment experiences / Tara E. Kent -- Sexual harassment on the Internet / Azy Barak -- "The rape" / Jeanne Murray Walker -- Real victims, reasonableness, and rape / Mary White Stewart -- Subcultural theory of rape revisited / Laura L. O'Toole -- What the West failed to learn about war from the "comfort women" / Margaret D. Stetz -- Undeclared war : African-American women writers explicating rape / Opal Palmer Adisa -- "To Judge Faolain, dead long enough : a summons" / Linda McCarriston -- Domestic violence : the intersection of gender and control / Michael P. Johnson -- Violence in intimate relationships : a feminist perspective / bell hooks -- Violence, gender, and elder abuse : toward a feminist analysis and practice / Terri Whittaker -- Domestic violence policy in the United States : contemporary issues / Susan L. Miller and LeeAnn Iovanni -- "The second photograph" / Margaret Randall -- Family violence, feminism, and social control / Linda Gordon -- Locating a secret problem : sexual violence in elementary and secondary schools / Nan D. Stein -- Men, masculinity, and child sexual abuse : a sex and gender question / Annie Cossins -- Child sexual abuse and the regulation of women : variations on a theme / Carol-Ann Hooper -- Who stole incest? / Louise Armstrong -- "Philadelphia story : September 1987" / Kathleen O'Toole -- Pornography, civil rights, and speech / Catharine MacKinnon -- Pornography and Black women's bodies / Patricia Hill Collins -- Pornography and the alienation of male sexuality / Harry Brod -- Problematizing the discourse : sex trafficking and ethnography / Anastasia M. Hudgins -- Prostitution as "choice" / Jane Anthony -- "Bessie Fenton : Redwing, 1888" / Kathryn Howd Machan -- Beyond the masculine mystique / Myriam Miedzian -- Supplanting linguistic violence / William C. Gay -- Coordinated community services for victims of violence / Patricia Yancey Martin -- Queering approaches to intimate partner violence / Elizabeth B. Erbaugh -- The impact of the sex industry in the European Union / Janice G. Raymond -- 10 things men can do to prevent gender violence / Jackson Katz -- Action / Elizabeth Ward